The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/ijms23052738
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Pharmacological Induction of Arterial Stiffness and Hypertension with Angiotensin II Does Not Affect Learning and Memory and Cerebral Amyloid Load in Two Murine Models of Alzheimer’s Disease

Abstract: Given the unprecedented rise in the world’s population, the prevalence of prominent age-related disorders, like cardiovascular disease and dementia, will further increase. Recent experimental and epidemiological evidence suggests a mechanistic overlap between cardiovascular disease and dementia with a specific focus on the linkage between arterial stiffness, a strong independent predictor of cardiovascular disease, and/or hypertension with Alzheimer’s disease. In the present study, we investigated whether phar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Indeed, increased arterial stiffness causes an excessive pulsatile energy in the brain microvascular bed due to insufficient flow wave damping, thus promoting the onset of microbleeds [ 85 ]. Studies on murine models also showed that the short-term pharmacological induction of arterial stiffness does not cause additional effects on mouse models of Alzheimer, suggesting a pathogenetic role of long-lasting arterial stiffness [ 86 ]. Recent studies also reported a positive association between local amyloid-β and regional tau burden and aortic stiffness [ 84 ], but its exact cause–effect relation deserves further studies.…”
Section: Increased Arterial Stiffness and Clinical Outcomementioning
confidence: 99%
“…Indeed, increased arterial stiffness causes an excessive pulsatile energy in the brain microvascular bed due to insufficient flow wave damping, thus promoting the onset of microbleeds [ 85 ]. Studies on murine models also showed that the short-term pharmacological induction of arterial stiffness does not cause additional effects on mouse models of Alzheimer, suggesting a pathogenetic role of long-lasting arterial stiffness [ 86 ]. Recent studies also reported a positive association between local amyloid-β and regional tau burden and aortic stiffness [ 84 ], but its exact cause–effect relation deserves further studies.…”
Section: Increased Arterial Stiffness and Clinical Outcomementioning
confidence: 99%